2023
DOI: 10.2196/51069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ChatGPT in Cantonese Sentiment Analysis: A Comparative Study (Preprint)

Ziru FU,
Yu Cheng Hsu,
Christian Shaunlyn Chan
et al.

Abstract: Background Sentiment analysis is a significant yet difficult task in natural language processing. The linguistic peculiarities of Cantonese, including its high similarity with Standard Chinese, its grammatical and lexical uniqueness, and its colloquialism and multilingualism, make it different from other languages and pose additional challenges to sentiment analysis. Recent advances in models such as ChatGPT offer potential viable solutions. Objective This study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…With no annotated data provided, ChatGPT achieved an F-measure of 0.8668, outperforming many commonly used off-the-shelf tools including VADER and the Linguistic Inquiry and Word Count (LIWC) 11 . Fu et al, evaluated ChatGPT on patient-generated texts in Cantonese through online counseling sessions and found that the zero-shot LLM can identify sentiments with over 90% accuracy, outperforming multiple machine learning models developed with annotated datasets 12 . Deiner et al evaluated GPTs’ capacity in rating the probabilities of tweets that indicate conjunctive outbreaks and found that GPT-4 had satisfying agreements with two human raters with Pearson correlation scores of 0.73 and 0.77 13 .…”
Section: Introductionmentioning
confidence: 99%
“…With no annotated data provided, ChatGPT achieved an F-measure of 0.8668, outperforming many commonly used off-the-shelf tools including VADER and the Linguistic Inquiry and Word Count (LIWC) 11 . Fu et al, evaluated ChatGPT on patient-generated texts in Cantonese through online counseling sessions and found that the zero-shot LLM can identify sentiments with over 90% accuracy, outperforming multiple machine learning models developed with annotated datasets 12 . Deiner et al evaluated GPTs’ capacity in rating the probabilities of tweets that indicate conjunctive outbreaks and found that GPT-4 had satisfying agreements with two human raters with Pearson correlation scores of 0.73 and 0.77 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This is an inevitable choice to adapt to technological trends, meet job market demands, respond to national educational policies, enhance international competitiveness, and promote scientific and technological innovation. The rise of interdisciplinary studies not only helps improve students' employability and innovation skills but is also significant for regional and national economic and technological development [7]- [8]. The integration of ChatGPT into the higher education system of Shandong Province, particularly in interdisciplinary teaching and research, signifies a major transformation in educational models and research methods [9]- [13].…”
Section: Introductionmentioning
confidence: 99%